Induction of Apoptosis by Newcastle Disease Virus Strains AF220 and V4-UPM in Human Promyelocytic Leukemia (HL60) and Human T- Lymphoblastic Leukemia (CEM -SS) Cells - Abu Bakar, Siti Aishah; Ali, Abd Manaf; Zawawi, Madihah; Ideris, Aini (2012)
Newcastle Disease Virus (NDV), an avian paramyxovirus, is a highly contagious, generalised virus disease of domestic poultry and wild birds characterized by gastro-intestinal, respiratory and nervous signs. In this study, it was shown that NDV strain AF2240 and V4-UPM are cytolytic to Human Promyelocytic Leukemia, HL60 and Human T-lymphoblastic Leukemia, CEM-SS cells. Results from MTT cytolytic assay showed that CD50 for NDV AF2240 against HL60 was 130 HAU and NDV V4-UPM against HL60 and CEM-SS were 110.6 and 150.9 HAU respectively. Besides, both strains were found to inhibit the proliferation of cells in a dose dependent manner. The mode of cell death either by apoptosis or necrosis was further analyzed using acridine orange and propidium iodide (AO/PI) staining. Our results showed that both NDV strains induced primarily apoptosis in treated cells at CD50 concentration. In conclusion, both NDV strains caused cytolytic effects primarily via apoptosis in leukemia cells.